MiR-21 Suppresses Anoikis through Targeting PDCD4 and PTEN in Human Esophageal Adenocarcinoma - Zhao, Meng-ya; Wang, La-mei; Liu, Jing; Huang, Xing; Liu, Jing; Zhang, Ya-fei (Current medical science, 2018)
Summary Anoikis is a form of apoptosis induced upon cell detachment from extracellular matrix. It has been determined that acquisition of resistance to anoikis is a critical step for tumor cell metastasis. MiR-21, the most prominent oncomiR, plays an important role in tumor progression. In this study, we revealed that up-regulation of miR-21 in human esophageal adenocarcinoma (EA) is associated with lymph node metastasis and poor survival rate. Because of the established anti-apoptosis effect of miR-21, it is tempting to speculate that miR-21 might contribute to tumor metastasis by regulating anoikis. qRT-PCR analysis demonstrated that miR-21 expression in OE33/AR cells (subpopulation of human EA OE33 cells that acquired resistance to anoikis) was significantly increased. Also, transfection of miR-21 mimics provided OE33 cells resisting to anoikis. By luciferase assays, we verified that PDCD4 and PTEN were the functional targets of miR-21. In mouse model, via tail vein injection experiment, we showed that the metastasis formation of OE33 cells in vivo could be mediated by changing the miR-21 expression pattern. Taken together, our findings suggested that miR-21 was involved in the regulation of anoikis in human EA cells. Targeting miR-21 may provide a novel strategy to prevent metastasis.